Synthesis of NaYF4:Yb3+, Tm3+ Nanocrystals Via the Thermal Decomposition Method Using Refined Sunflower Oil - Smelkovs, Lukass; Vīksna, V.; Teterovskis, Janis; Grube, Jurgis (Sciendo, 2023)
In recent years, up-conversion luminescence nanoparticles have attracted significant attention from researchers in fields such as analytical chemistry (for example qualitative and quantitative analysis of metal and non-metal ions) and biomedicine (cancer imaging, drug delivery, treatment, etc.) due to their high rate of emission efficiency, easy surface functionalization, great chemical and thermal and photostability and other favorable properties. NaYF4 in particular has attracted interest of researchers as a host material due to its low phonon energy, thus increasing the efficiency of emission. In this study, the synthesis of NaYF4:Yb3+,Tm3+ nanocrystals using the hydrothermal method was successfully carried out. Refined sunflower oil containing oleic acid was used as a solvent instead of analytical grade oleic acid and octadecene-1, reducing the cost of the synthesis. Using semi-quantitative XRD measurement analysis, it was determined that 25.3 % hexagonal β-NaYF4:Yb3+,Tm3+ as well as 23.8 % cubic α-NaYF4 nanocrystal crystalline phases were found in the synthesized sample. The sample showed mainly luminescent characteristics typical of hexagonal NaYF4:Yb3+,Tm3+ lattice nanoparticles. --//-- This is an open access article Smelkovs, L., Viksna, V., Teterovskis, J. and Grube, J.. "Synthesis of NaYF4:Yb3+, Tm3+ Nanocrystals Via the Thermal Decomposition Method Using Refined Sunflower Oil" Latvian Journal of Physics and Technical Sciences, vol.60, no.5, 2023, pp.22-31. https://doi.org/10.2478/lpts-2023-0028 published under the CC BY-NC-ND 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; NaYF4:Yb3+, Tm3+; refined sunflower oil; thermal decomposition; up-conversion luminescence